Quantification of Microplastics in Urban Compost-Amended Farmland Soil Using an Elutriation Device - Luigi Paolo D’Acqui; Sara Di Lonardo; Martina Grattacaso; Alessandra Bonetti; Ottorino-Luca Pantani (Agronomy)
Microplastics (MPs) present in farmland soils, where urban compost has been distributed since 2005, were extracted using a device based on elutriation, a method developed for marine sediments but not yet used in soil. Since (i) fine earth (diameter < 2 mm) is the standard fraction used for soil analysis and (ii) the size of MPs contained in urban compost may exceed that value, MP were recovered from both the entire soil and fine earth. The recovered MPs pieces were weighed, counted, and characterized using FTIR photoacoustic spectroscopy (FTIR-PAS). Both the mass and number of recovered MPs pieces (>34 µm) were comparable to those reported in the literature for soils. Polystyrene, polyethylene, and polypropylene are the primary polymers. Nevertheless, some issues were highlighted: (i) the importance of sampling the soil by volume, and (ii) the need of analyzing the entire soil sample rather than just the fraction below 2 mm, commonly used in soil analysis; (iii) the necessity of breaking up (i.e., by ultrasonication and/or dispersion) soil aggregates that may withstand the elutriation process.